Assessment of heavy metals concentration in groundwater and their associated health risks near an industrial area - Bahareh Lorestani; Hajar Merrikhpour; Mehrdad Cheraghi (Environmental Health Engineering and Management, 2020)
Background: Heavy metals (HMs) contamination from industrial wastewater is a major environmental problem that has been increasing in the past few years. The purpose of this study was to investigate the current status of HMs contamination in Bu-Ali industrial town, Hamedan, western Iran. Methods: The concentration of 9 serious HMs (arsenic, cadmium, chromium, copper, iron, lead, manganese, nickel, and zinc) in groundwater samples was studied during spring 2017. In order to evaluate water quality for aquaculture and drinking purposes, heavy metal evaluation index (HEI), heavy metal pollution index (HPI), and contamination (Cd) indicator were calculated. Health risk of HMs was also calculated to assess the risk of cancer. Results: The results showed that the mean concentration of the HMs according to the Cd index was as follows: Pb > Ni > Cr > Fe > Cd > As > Cu > Zn > Mn. The mean HEI and HPI values were 89.1 and 815.5, respectively. The results also showed that there was no relationship between the HMs concentration and cancer risk. Conclusion: The concentration of the studied HMs in most samples was higher than the permissible limit for drinking water. The HEI and HPI values in high-risk samples were higher than the permissible limit of drinking water, therefore, there is high risk and limitation for aquatic life, but there is no risk of cancer.